Распространение волн в периодических жидкотвердых слоистых средах - Роганов, Ю.В.; Роганов, В.Ю. (Геофизический журнал, 2016)
Виведено дисперсійне рівняння для хвиль Флоке, що поширюються в бінарному горизонтально-шаруватому рідкотвердому середовищі. Дисперсйне рівняння представлено добутком чотирьох множників, що дає змогу пояснити розбиття області параметрів (частота, горизонтальна повільність) на зони проходження і поглинання. Показано, що перехід цих множників у нуль відповідає хвилям Флоке з горизонтальною груповою швидкістю. Розглянуто властивості хвиль, що поширюються горизонтально. Отримано формули для відношень компонент векторів поляризації і амплітуд парціальних хвиль. Теорію проілюстровано на одному прикладі Dispersion equation is derived for the Floquet waves in a horizontal periodically layered fluidsolid medium. It is shown that the dispersion equation consists of four factors. This representation explains the splitting of parameters (frequency, horizontal slowness) in passing and stop bands. The Floquet waves with horizontal group velocity can be computed individually from each of these factors. The properties of horizontally propagated waves are considered. The equations for the ratios of the components of polarization vectors and the amplitudes of partial waves are derived. Proposed theory is illustrated in one numerical example.